Budgeting and Analysis of Social Service Providing Institutions: the Case of Care Homes - Miškinienė, Renata; Nariūnaitė, Andželika; Basiulis, Katažyna; Straigė, Milda (Buhalterinės apskaitos teorija ir praktika, 2024)
One of the main functions of social protection is the provision of social services to peoplewho need them. In today's society, the need for social services tends to increase and needs to beadequately funded. However, the issues of the management and financing of these services have notbeen sufficiently investigated. In order to fill this gap, this article examines the financing arrangementsfor social services. It also analyses and evaluates the preparation and implementation of the budget ofthe institution providing such services. The object of the study is the budget for 2020-2022 of one of theinstitutions providing social services – care homes. The aim of the study: after examining the nature ofsocial services and the arrangements for their management and financing, to assess the arrangementsfor preparing the budget of the care home and to analyse it budget for the period 2020-2022. The studyfound that the projected revenue and cost budget of the care home is quite different from the actualrevenue and cost of the institution. The study identified the reasons for these variances and madesuggestions for improving the preparation of the budget project with a view to reducing the variancesbetween planned and actual amounts in future.